Functional loss of ubiquitin‐specific protease 14 may lead to a novel distal arthrogryposis phenotype. Issue 4 (31st January 2022) - Turgut, Gozde Tutku; Altunoglu, Umut; Sivrikoz, Tugba Sarac; Toksoy, Guven; Kalaycı, Tuğba; Avcı, Şahin; Karaman, Birsen; Gulec, Cagri; Başaran, Seher; Sayın, Gözde Yeşil; Kayserili, Hulya; Uyguner, Zehra Oya
Abstract: Multiple congenital contractures (MCC) comprise a number of rare, non‐progressive conditions displaying marked phenotypic and etiologic heterogeneity. A genetic cause can be established in approximately half of the affected individuals, attributed to genetic defects in the formation and functioning of the central and peripheral nervous system, neuromuscular junctions, skeletal muscles, and connective tissue. Ubiquitin‐specific protease 14 ( USP14 ) encodes a major proteasome‐associated deubiquitinating enzyme with an established dual role as an inhibitor and an activator of proteolysis, maintaining protein homeostasis. Usp14 ‐deficient mice show a phenotype similar to lethal human MCC phenotypes, with callosal anomalies, muscle wasting, and early lethality, attributed to neuromuscular junction defects due to decreased monomeric ubiquitin pool. We describe a new, autosomal recessive MCC phenotype in three fetuses from two different branches of a consanguineous family, presenting with distal arthrogryposis, underdevelopment of the corpus callosum, and dysmorphic facial features. Exome sequencing identified a biallelic 4‐bp deletion (c.233_236delTTCC; p.Leu78Glnfs*11, SCV002028347) in USP14, and sequencing of family members showed segregation with the phenotype. RT‐qPCR experiment in an unaffected heterozygote revealed that mutant USP14 was expressed, indicating that abnormal transcript escapes nonsense‐mediated mRNA decay. We propose that herein described fetuses represent the first human phenotype of USP14 loss, with callosal anomalies and/or cortical malformations, multiple contractures, and recognizable dysmorphic facial features. Abstract : Three fetuses, affected with a new autosomal recessive distal arthrogryposis phenotype with underdevelopment of the corpus callosum and dysmorphic facial features, were shown to harbor a biallelic 4‐bp deletion (c.233_236delTTCC; p.Leu78Glnfs*11) in USP14 . Previous studies in Usp14 mouse models demonstrated similar phenotypic characteristics. qPCR experiment in a carrier individual indicated that abnormal transcript escaped nonsense‐mediated mRNA decay.